'Politics done like science': Critical perspectives on psychological governance and the experimental state. (April 2018) - Jones, Rhys; Whitehead, Mark
There has been a growing academic recognition of the increasing significance of psychologically – and behaviourally – informed modes of governance in recent years in a variety of different states. We contend that this academic research has neglected one important theme, namely the growing use of experiments as a way of developing and testing novel policies. Drawing on extensive qualitative and documentary research, this paper develops critical perspectives on the impacts of the psychological sciences on public policy, and considers more broadly the changing experimental form of modern states. The tendency for emerging forms of experimental governance to be predicated on very narrow, socially disempowering, visions of experimental knowledge production is critiqued. We delineate how psychological governance and emerging forms of experimental subjectivity have the potential to enable more empowering and progressive state forms and subjectivities to emerge through more open and collective forms of experimentation.